Zmiany przepisów o zobowiązaniach podatkowych - Gomułowicz, Andrzej (Wydział Prawa i Administracji UAM, 1982)
Legally effective for the last thirty years, the provisions of the Decree of Oct. 26, 1956 are presently found to be obsolete to a considerable degree. They comply with the conditions of the forties and fifties. Legal and financial institutions of this regulation as well as its wording required adjustments to current socio-economic conditions and legal position. These postulates have been satisfied by virtue of the Act of Dec. 19, 1980, of Liabilities to Pay Taxes. A different regulation of several questions was introduced in the new law. The following provisions are to be numbered among the controversial matters: authority of administration for a taxpayer's house search and simultaneously not mentioning of explicit premises to be satisfied to create grounds for the search, retention of an institution of taxation at estimate. The substantial changes involve a different treatment of such problems as dates of settlement of tax liabilities and of their extinction, overpayment of the tax and the interest on it, limitation rules of tax liabilities, liability of a taxpayer's spouse, his family members and third persons to pay his taxes, explicit definitions of the subject matter of taxation and of persons coming within the scope of this law, unification of dates of payment for the taxpayers. Too numerous delegacies of legislative power and the fact that the new act will be in force for the following year side by side with the hitherto existing implementing regulations have to be considered as the shortcomings of the tax liability laws.
Change of Regulation of Liabilities Pay Taxes